(untitled) (World Economics and Finance Bulletin, 2023)
The article discusses the theoretical aspects of the study of the production infrastructure of the region: the essence of the concepts of "infrastructure" and "industrial infrastructure" is revealed, the signs, functions and principles of an effective system of the production infrastructure of the region are formulated.